Systematic review and meta-analysis on prevalence, pattern, and factors associated with ocular protection practices among welders in sub-Saharan Africa - Atalay, Yibeltal Assefa; Gebeyehu, Natnael Atnafu; Gelaw, Kelemu Abebe (Frontiers in Public Health, 2024)
BACKGROUND: Due to hazardous working conditions, welders are more likely to be exposed to mild to severe eye issues during the welding process. Globally, this issue is a major contributor to vision loss and blindness. One of the most frequent causes of unilateral blindness in the globe is ocular injury.This review aimed to assess the pooled prevalence of ocular protection practice and associated factors among welders in sub-Saharan Africa.Databases including PubMed, Scopus, web of Science, Google Scholar, and the African Journals Online were systematically searched for relevant literature. The statistical analysis was performed using STATA data analysis software version 14, while Microsoft Excel was used for data abstraction. We checked publication bias using a funnel plot and Egger and Begg regression tests. A p-value < 0.05 was considered significant, suggesting the presence of presence publication bias. The I 2 statistics were used to assess heterogeneity between studies. The study's overall effect was evaluated using the random effects model.From retrieved 2,326 original studies, 17 studies were included in the final pooled prevalence analysis. The overall prevalence of ocular protection practice among small-scale